Study Description of Student Nursing Barriers in Online Learning during the Covid-19 Pandemic - Syafrisar Meri Agritubella (International Journal of Advanced Health Science and Technology, 2022)
The paradigm shift during the Covid-19 pandemic requires educational institutions to follow current technological developments. Online learning is the main choice to avoid the spread of the virus. The purpose of the study was to determine the inhibiting factors for online learning in nursing students. This type of research is descriptive study. The population is all nursing students with Total Sampling technique. The sample criteria are nursing students, willing to be respondents, in good health, not in clinical practice. The number of samples in this study was 209 people. Data collection through questionnaires using the Google Form application. The author sent an electronic survey via WhatsApp Group (WAG) students from April 1 to June 30, 2020. The questionnaire used a combination of multiple choice, Likert scale, and open-ended questions containing demographics (gender and level of education), barriers to online learning, and access to technology. The results of the univariate analysis through the frequency distribution are obtained that majority of respondents are female (94.3%), majority of respondents are DIII Nursing (92.3%), the inhibiting factors consisted of internet instability (54.5 %), power outages (89%), smartphones that were not supported (44%), Tech stuttering (58.9%), insufficient quota subsidies from campus (35.6 %) and parental support have not been maximized (43.1%). Conclusion: the most important inhibiting factor for online learning is power outages. The need for online application socialization and support for adequate facilities and infrastructure at home. For future research, it is recommended to study the effect of online learning in improving student competencies and attitudes. To improve optimal online learning at home, I hope that there will be family motivation so that students can follow the learning process to completion.